PENGARUH KONSENTRASI HYDROXYPROPYL METHYLCELLULOSE SEBAGAI BAHAN PENGIKAT PADA SEDIAAN TABLET EKSTRAK RIMPANG JAHE MERAH (zingiber officinale Var. Rubrum.) - Nur AIn Thomas; Muhammad Taupik; Nur Oktaviana; Widy Susanti Abdulkadir (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Lozenges are solid preparations made from aromatic and sweet taste that can dissolve slowly in the mouth, which are intended to treat infections in the mouth and throat. Hydroxypropyl Methylcellulose (HPMC) is a binder that can be used in lozenges.This study attempted to examine the effect of the concentration of HPMC as a binder in the tablet preparation of red ginger rhizome extract (Zingiber officinale Var Rubrum) by wet granulation method. This study was a laboratory experimental study by comparing the three concentrations of HPMC binder used in each formula i.e., FI (4%), FII (5%), FIII (6%).The resulting tablets were tested for physical properties including organoleptic tests, weight uniformity, tablet hardness, tablet friability and hedonic tests. Based on the results of the study, it was shown that with an increase in the concentration of the HPMC binder, the physical quality of the resulting tablet also increased. The higher the concentration of HPMC used, the better the uniformity of weight and the high level of tablet hardness. However, tablet friability will decrease. The results showed that the concentrations of 4%, 5%, and 6% had an effect on the tablet physical properties whichwas fragility. Further, formula II with a concentration of 5% had better tablet physical quality and was preferred by respondentsbased on hedonic tests.